Weird Animals - Parker; Steve (Essex Miles Kelly, 2013)
It is a children's non-fiction book that explores the strange and unusual aspects of various animals. The book is designed to captivate young readers with fascinating facts and vibrant illustrations of creatures with unique characteristics and behaviors